ANALISIS PERENCANAAN LAPIS TAMBAH PERKERASAN JALAN KAIYA – MAELANG PROVINSI SULAWESI UTARA - Muhammad Aidil; Andi Sulfanita (UKI Press, 2026)
The increase in traffic volume, particularly heavy vehicles, can reduce the structural performance of road pavements, making appropriate maintenance measures necessary to maintain road serviceability. The Kaiya–Maelang Road section in North Sulawesi is part of the main Trans Sulawesi corridor and plays an important role in supporting community mobility and goods distribution. This study aims to analyze the required overlay thickness on the Kaiya–Maelang Road section to maintain pavement structural performance throughout its design life. The research employed a quantitative approach using pavement rebound deflection data obtained from Benkelman Beam testing at Stations 7+000 to 9+000 and average daily traffic (ADT) data. Overlay thickness was analyzed based on the 2024 Road Pavement Design Manual (MDP 2024) by considering maximum deflection, deflection curvature, and planned traffic loading expressed as Cumulative Equivalent Standard Axle (CESA). The results showed that the traffic volume of 13,982 vehicles per day with an annual growth rate of 4.75% produced a CESA value of 8.11 million for a 10-year design life. The maximum deflection value was 0.817 mm, while the adjusted Falling Weight Deflectometer (FWD) deflection value was 0.488 mm. Although no indication of permanent deformation was identified, fatigue cracking analysis indicated the need for overlay treatment. The analysis concluded that a total overlay thickness of 150 mm is required, consisting of a 70 mm Asphalt Concrete–Wearing Course (AC-WC) layer and an 80 mm Asphalt Concrete–Binder Course (AC-BC) layer. This overlay thickness is considered adequate to maintain the structural performance of the pavement throughout the design life. Keywords: Planning analysis; Overlay; Road paving.